Immune Thrombocytopenia Following Dengue Fever - Madhumita Nandi; Nikhil Gupta (Dubai Medical Journal)
Introduction: Dengue is an endemic mosquito-borne infection in tropical countries. The manifestations vary from asymptomatic infection to classic dengue fever, to more critical forms like dengue hemorrhagic fever and dengue shock syndrome. The critical phase occurs typically within the timeline of 4-7 days from the onset of symptoms.